Bioassay-guided isolation of antibiotics from selected marine fungi - Chow, Ngai Teng. (Universiti Malaysia Sarawak, (UNIMAS), 2011)
The emcrgence and widespread of multidrug rcsistant (MDR) bacteria has led to high demands for ,the development of new and effective antibiotics. Hence, a study was devised to scrcen for antibacterial activity in selectcd marine fungi. Three selected fungi, which were P 1.2.1, PS.l.l and PI 0.2.1, were revivcd and subcultured before being identified and characterized using microscopic examination of slide culture. Fungal isolate P 1.2.2 was identified to be the Drepanoconis sp. while isolates PS.l.l and PI 0.2.1 were identified to be the Penicillium sp. The fungal isolatcs were subjected to preliminary screcning against Gram-positive bacteria, Staphylococcus aureus, Salmonella typhi, and Enterobacter aerogenes, and Gram-negative bacteria, Escherichia coli. Isolate P 1.2.1 showed the most potential of producing antibacterial substances with the inhibition zones formed against all the test bacteria. The largest zones of inhibition were observed when isolate P 1.2.1 was tested against Staphylococcus aureus and Enterobacter aerogenes. Subsequently, antibiotic extractions from isolate P1.2.1 was carried out using several solvents, which were hexane, chloroform, dichloromethane, ethyl acetate, methanol, and water. Further screening using agar disc diffusion technique, dichloromethane extract of isolate P 1.2.1 showed antibacterial activity against Enterobacter aerogenes, with the MIC value of 1mg/ml. The result showed that marine microorganisms are capable of producing antibiotic substances. Further study is required to scale up the extraction process, and to concentrate the antibiotics extracted.